Effective Arabic Language Teaching Strategies in the Language Laboratory for Students of Darussalam Gontor Islamic Institution - Huda, Rofiazka Fahmi (Ad-Dhuha, 2023)
Language is an important tool for the life of civilized man. Through language, people can communicate with each other, and convey their intentions and feelings to others. The modern factor used by Dar Al Salam Institute for teaching Arabic and English is the language lab. The language officials in the language lab have made effective teaching strategies to make teaching Arabic and English effective and good for training listening, writing, speaking and other exercises. Based on the above, the research aims to reveal the effective Arabic language teaching strategy in the language lab for the institute's students, and what problems the language supervisors faced as lab organizers when teaching the language daily, and how to solve those problems completely. From the research results obtained by the researcher, the strategy for teaching Arabic in the language lab for beginners is: 1) Watching films programmed for the Arabic language, 2) Giving vocabulary or styles before watching, 3) Pronouncing new words or styles with the students, 4) Writing sentences or vocabulary with their full meanings. The strategy for teaching Arabic at the intermediate level is: 1) Watching films programmed for the Arabic language, 2) Taking words or styles from watching films, 3) Searching for the meanings of new words, vocabulary or styles in Arabic dictionaries, 4) Having the teacher teach new vocabulary that the students did not find, 5) Taking the short meaning from watching the film programmed for the Arabic language, 6) Writing sentences or vocabulary with their full meanings. As for the problems faced by language officials in teaching Arabic in the language lab, they are that the educational curriculum in the language lab did not contribute to implanting the language in the souls of the students, because the materials are sometimes not suitable for the level of understanding of the students between the first and sixth year students, and the factors of teaching the language in the language lab are the discs that contain incomplete language materials and sometimes do not match the world of the students’ affairs. The solutions to these problems are to teach Arabic in the language lab according to the students’ ability to master the Arabic language. According to the students’ ability to master the Arabic language, before participating, they must first take an exam. From this exam, the students’ proficiency in the Arabic language is known, and then the group is divided into beginners, intermediate, and advanced, not according to the prescribed classes.